INTEGRATING NORTH CYPRUS INTO THE EU - Arslan, Kaya (Turkish Policy Quarterly, 2005)
In the aftermath of the referenda in Cyprus, the UN and the EU made commitments for the lifting of economic embargoes and all forms of unnecessary restrictions imposed upon the Turkish Cypriots. The Turkish Cypriots are still waiting for the obstacles which have adversely affected their life for over 40 years to be lifted. This paper explores the political, legal, social and economic aspects of life in North Cyprus, along with the potential implications of integrating North Cyprus into the EU by developing economic relations.